Features of the anatomic structure of the medicinal plant Rhodiola rosea L. in East Kazakhstan (Experimental biology, 2021)
In this article, in the study of the anatomical structure of the roots, the identification of diagnosticsigns is considered – perennial, herbaceous, very valuable medicinal plants Rhodiola rosea L, a speciesof the genus Rhodiola, the Crassulaceae family. In the future, we focus on the conservation and rationaluse of Rhodiola rosea L., one of the most valuable and rare medicinal plants, for the conservation ofcertain plant species, and replenishment of the genetic fund of this species. Rhodiola rosea L., popularlycalled the golden root, since the roots have a yellow golden color and have an ancient meaning in folkmedicine.Despite the specific chemical composition, the official article in the State Pharmacopoeia ofthe Republic of Kazakhstan is not registered, primarily grows in Kazakhstan. The main objective of thestudy is to study the anatomical features of plants of Rhodiola rosea L.Based on the study, the anatomical features of the leaves, stems and transverse sections of the rootswere identified, motor cells in the epidermis of the leaves, cleavage and concentration of tannins onthe stems, the location of starchy crystals in the root rhytidoma, in the nucleus parenchyma were established.When determining the location of biologically active substances in Rhodiola rosea L., tanninswere first detected in idioblasts.
Keywords: Rhodiola rosea L., morphology, root, anatomy, xylem, phloem.